Cancellation of Marriage due to Negligence and Legal Consequences (Case Study on the Decision of the Pandeglang Religious Court, Banten No. 84/Pdt.G/2013/PA.Pdlg) - Sanusi, Ahmad; Somawinata, Yusuf; Anwar, Khoirul; Jamaluddin, Jamaluddin; Rahman, Arif (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
According to the Marriage Law, a person who will get married must meet the requirements and marriage principles as stipulated in their respective religions and beliefs as well as the administrative requirements. However, sometimes marriage registration process is not fully fulfilled, which then leads to the cancellation of the marriage. Marriage annulment is the cancellation of a husband and wife relationship after the marriage contract is held. The cancellation process may be carried out by the religious court if the parties do not meet the requirements to carry out the marriage, as stated in Article 22 of Law no. 1 of 1974 concerning marriage. This study will analyze the decision to annul the marriage and its legal consequences at the Pandeglang Religious Court. The research used content analysis, which is to analyze descriptively the content of court decisions with a normative approach. The results of this study are that the panel of judges granted the application for annulment of marriage with legal considerations and the existence of obstacles to marriage because it was contrary to the principle of marriage itself, namely the principle of monogamy. The reason was the Petitioner's negligence and the manipulation of Respondent I and Respondent II in attaching the administrative requirements of their marriage, in which the marriage occurred when Respondent I still had a legal wife. The annulment of the marriage leads to legal consequences for the child, and the assets possed during the marriage, as well as third parties. Thus, the annulment of marriage does not have a retroactive effect on the position of the child and third parties.